Why and How Is Compassion Necessary to Provide Good Quality Healthcare? - Marianna Fotaki (Kerman University of Medical Sciences, 2015)
Recent disclosures of failures of care in the National Health Service (NHS) in England have led to debates about compassion deficits disallowing health professionals to provide high quality responsive care. While the link between high quality care and compassion is often taken for granted, it is less obvious how compassion - often originating in the individual's emotional response - can become a moral sentiment and lead to developing a system of norms and values underpinning ethics of care. In this editorial, I argue why and how compassion might become a foundation of ethics guiding health professionals and a basis for ethics of care in health service organisations. I conclude by discussing a recent case of prominent healthcare failure in the NHS to highlight the relationship between compassion as an aspect of professional ethics on the one hand, and values and norms that institutions and specific policies promote on the other hand.